2002
DOI: 10.1590/s0036-46652002000300006
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis caused by Leishmania (Viannia) braziliensis in a patient infected with human immunodeficiency virus

Abstract: The current article reports the case of a 19-month-old-girl, from the state of Minas Gerais, Brazil, with visceral leishmaniasis, by Leishmania (Viannia) braziliensis, and Human Immunodeficiency Virus (HIV) co-infection. The child's mother and father, aged 22 and 27 years old, respectively, were both HIV positive. The child was admitted to the General Pediatric Center, in Belo Horizonte, presenting high fever, fatigue, weight loss and enlargement of liver and spleen. Indirect immunofluorescent test revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 24 publications
1
16
0
7
Order By: Relevance
“…We have recently observed that Sb(III)-resistant amastigotes of L. panamensis and L. infantum are crossresistant to Sb(V) when grown inside of macrophages, whereas Sb(III) is highly leishmanicidal against both forms of the parasite. 2 Previous studies found no correlation between clinical response and in vitro resistance to Sb(V) with the promastigote stage of the parasite (31); however, a correlation was observed with intracellular parasites (31). Interestingly, we also observed a correlation between resistance to Sb(III) and to As(III) in both promastigotes and intracellular amastigotes (Table II).…”
Section: Identification and Cloning Of Lmaqp1-the Leishmaniasupporting
confidence: 43%
See 2 more Smart Citations
“…We have recently observed that Sb(III)-resistant amastigotes of L. panamensis and L. infantum are crossresistant to Sb(V) when grown inside of macrophages, whereas Sb(III) is highly leishmanicidal against both forms of the parasite. 2 Previous studies found no correlation between clinical response and in vitro resistance to Sb(V) with the promastigote stage of the parasite (31); however, a correlation was observed with intracellular parasites (31). Interestingly, we also observed a correlation between resistance to Sb(III) and to As(III) in both promastigotes and intracellular amastigotes (Table II).…”
Section: Identification and Cloning Of Lmaqp1-the Leishmaniasupporting
confidence: 43%
“…The mechanisms of resistance in some of these strains have been determined, and there is considerable diversity in the causes of resistance (37). 2 This suggests that increasing expression of AQP1 can reverse resistance in diverse backgrounds of resistance. …”
Section: Identification and Cloning Of Lmaqp1-the Leishmaniamentioning
confidence: 99%
See 1 more Smart Citation
“…A identificação das espécies de Leishmania que circulam em determinado foco de transmissão, particularmente em regiões onde as diferentes formas clínicas ocorrem simultaneamente, é muito importante para o conhecimento da epidemiologia das leishmanioses e planejamento de estratégias de controle 2 . Tratando-se de leishmaniose visceral nas Américas, a única espécie considerada responsável pela doença é Leishmania (Leishmania) chagasi, embora já se tenha descrito Leishmania (Leishmania) amazonensis 5 e Leishmania (Viannia) braziliensis 48 49 52 , em diagnóstico humano 47 , canino 20 44 e em flebotomíneos 24 35 36 , sendo também útil na caracterização de isolados humanos 37 .…”
Section: Artigo/articleunclassified
“…São 11 as espécies de Leishmania identificadas como patogênicas para o homem e estão relacionadas a acometimento de tegumentos ou vísceras, porém em alguns casos descritos em pacientes imunodeprimidos, se encontra acometimento de pele na leishmaniose visceral (Francês et al, 1984;Postigo et al, 1990;Russo et al, 2003), assim como raros casos de disseminação a vísceras a partir de lesões tegumentares (Silva et al, 2002).…”
Section: Aidsunclassified